Participant experiences in a feasibility trial of supervised exercise training in adults with venous leg ulcers: A qualitative study. Issue 6 (13th October 2019) - Kesterton, Sue; Crank, Helen J.; Tew, Garry A.; Michaels, Jonathan; Gumber, Anil; McIntosh, Emma; King, Brenda; Klonizakis, Markos
Abstract: Exercise training can improve lower‐limb cutaneous microvascular reactivity in adults with venous leg ulceration; however, there is a lack of research on patients' views about the acceptability and feasibility of exercise interventions. The aim of this study was to explore participants' experiences of the trial "Exploring the Feasibility of Implementing a Supervised Exercise Training and Compression Hosiery Intervention in Patients with Venous Ulceration" (FISCU). Semi‐structured face‐to‐face and telephone interviews were used to investigate participants' experiences (n = 16) of taking part in the FISCU trial. Data were analysed using thematic analysis. Three overarching themes were identified, along with 11 sub‐themes: (a) sedentary cautious living (because of pain and reduced mobility, treatment and perceived control, and advice to rest and be careful), (b) key components of the exercise trial (including motivation, an individualised intervention supervised by a specialist exercise professional, and satisfaction with the intervention), and (c) benefits of exercise (physical benefits and healing, psychological well‐being, positive impact on comorbidities, and an improved self‐management strategy). This study found that an exercise intervention was viewed by participants as positive, acceptable, and feasible while living with a venous leg ulcer. An individualised and supervised exercise programme was key to build confidence to exercise.